2020
DOI: 10.3390/su12229347
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and Employability: The Mediational Role of Ambition and a Protean Career among Unemployed People

Abstract: Literature on job searching suggests that emotion regulation has an impact on employability, but this relationship is far from being explained; furthermore, most of the studies have been conducted among students or workers. The aim of the current study was to investigate the relationship between emotion regulation and employability among unemployed people, analyzing the role of ambition and protean career orientation as possible factors in such a relationship. Participants were 228 unemployed subjects who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…The last hypothesis proposes that some socioemotional competencies of teachers (Empathy, Regulation, Prosociality and Emotional Autonomy) are related to their levels of burnout. The background shows that Empathy and Prosociality play a key role in improving work performance and prevent against teacher absenteeism, which can be observed in their relationships with Professional Efficacy [49,53]. Both socioemotional competencies are essential to increase interpersonal skills at work, as well as Regulation, which is negatively related to the three dimensions of burnout, since it is a protective factor against adverse situations, as is the case of the COVID-19 pandemic [15], as well as Emotional Autonomy [42,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The last hypothesis proposes that some socioemotional competencies of teachers (Empathy, Regulation, Prosociality and Emotional Autonomy) are related to their levels of burnout. The background shows that Empathy and Prosociality play a key role in improving work performance and prevent against teacher absenteeism, which can be observed in their relationships with Professional Efficacy [49,53]. Both socioemotional competencies are essential to increase interpersonal skills at work, as well as Regulation, which is negatively related to the three dimensions of burnout, since it is a protective factor against adverse situations, as is the case of the COVID-19 pandemic [15], as well as Emotional Autonomy [42,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…This factor is conceived as the individual's willingness and commitment to achieve their professional goals and the adoption of concrete actions to realize them and to take into account the importance of a career for personal self-realization. In addition to employability, career ambition is a strong predictor of successful career development [36] and protean career orientation [37]. Moreover, research has suggested that individuals higher in career ambition are more resilient to stress [38] and experience greater mental well-being [29].…”
Section: Antecedents Of Self-perceived Employabilitymentioning
confidence: 99%
“…Furthermore, when the protean career orientation is adopted, employability is more effectively used in job searching, because unemployed become more aware of their values, projects, technical and soft skills and develop proactive career strategies (Panari et al, 2020 ). This perspective can maintain a positive sense of personal professional identity whilst focusing on solutions to get out of the social disadvantage, rather than on the causes of the unemployment situation.…”
Section: Discussionmentioning
confidence: 99%